Differential Response Of Rice Cultivators to Potash Application In The Rice Soil Of Onattukara - Shaji KV (Department of Soil Science and Agricultural Chemistry, College of Agriculture, 1996)
It is known that there exists varietal differences in tolerance to nutrient deficiency conditions among rice cultivars. The sandy soils of Onattukara region is inherently deficient in K which resulted in a higher POP recommendation for rice in terms of K application. So to exploit the varietal differences of rice in deficiency tolerance of K, a field experiment was undertaken to screen 48 rice cultivars belonging to tall indicas and dwarf high yielding groups of varying growth durations. The experiment was laid in 384 microplots in "Group Balanced. Block in Split Plot Design" with four K levels and two replications. The various growth and yield attributes and yield were studied with a view to locate varieties which could produce similar yields even at lower levels of K. The results indicated that in general the varietal influences on most of the growth characters in all the four groups were profound. Moreover positive and significant effect of K doses were observed. However LAI showed no variation with differing levels of K. Differential response of varieties to varying K doses as manifested by root spread was considerable only in medium duration varieties while